Considering the (Un)observed: temporary agency work in productivity estimations - Alexander Schiersch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The study focuses on the question of whether or not productivity estimates are biased due to the emergence of a new input that is usually omitted: temporary agency worker (TAW). The study analyzes labor productivity and TFP by means of a structural approach using a representative dataset of German manufacturing firms. The empirical results show, once TAW is taken into account, that: i) labor productivity in most manufacturing sectors is significantly lower; ii) average TFP differs significantly in most sectors; but iii) the coefficients for regular labor are not significantly different between estimations with and without TAW.
Keywords: D24; J24; L60; 330